A Case Report on Acanthomatous Ameloblastoma of the Anterior Mandible with Brief Review on Advanced Imaging Diagnosis - Chinam, Nivedita; Vaidya, Aniket; Khorate, Manisha; Khurana, Sonam (Indian Journal of Radiology and Imaging, 2021)
Ameloblastoma is the most common benign odontogenic tumor of epithelial origin. It exhibits a locally aggressive behavior and high recurrence rate with multitude of factors involving in its molecular pathogenesis. This article reports a case of acanthomatous ameloblastoma involving the mandible in a 60-year-old male patient with peculiar imaging characteristics. The role of computed tomography and magnetic resonance imaging in diagnosis of conventional ameloblastoma has been elaborately emphasized in the discussion. Although the final diagnosis is based on histopathological features, physicians should be aware of the role of advanced imaging for diagnosis of ameloblastoma and for better surgical management.
Keywords: ameloblastoma; imaging; neoplasm; odontogenic tumor